2023
DOI: 10.1111/imr.13279
|View full text |Cite
|
Sign up to set email alerts
|

PANoptosis: Mechanisms, biology, and role in disease

Xu Sun,
Yanpeng Yang,
Xiaona Meng
et al.

Abstract: SummaryCell death can be executed through distinct subroutines. PANoptosis is a unique inflammatory cell death modality involving the interactions between pyroptosis, apoptosis, and necroptosis, which can be mediated by multifaceted PANoptosome complexes assembled via integrating components from other cell death modalities. There is growing interest in the process and function of PANoptosis. Accumulating evidence suggests that PANoptosis occurs under diverse stimuli, for example, viral or bacterial infection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 193 publications
(353 reference statements)
0
2
0
Order By: Relevance
“…Recently, the PANoptosis combining key characteristics of pyroptosis, apoptosis and necroptosis was proposed, and this cell-death mode occurred in response to multiple stimuli such as viral/bacterial infections, cytokine storms and cancers. 41 Studies showed that PANoptosis could be triggered by ultrasound irradiation and had great advantages in tumor suppressions. 42 However, the cell apoptosis reported in our study has proved a major mode which induced an efficacious sonodynamic therapy by the experimental parameters (frequency: 1.0 MHz, duty cycle: 50%, power density: 1.0 W cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the PANoptosis combining key characteristics of pyroptosis, apoptosis and necroptosis was proposed, and this cell-death mode occurred in response to multiple stimuli such as viral/bacterial infections, cytokine storms and cancers. 41 Studies showed that PANoptosis could be triggered by ultrasound irradiation and had great advantages in tumor suppressions. 42 However, the cell apoptosis reported in our study has proved a major mode which induced an efficacious sonodynamic therapy by the experimental parameters (frequency: 1.0 MHz, duty cycle: 50%, power density: 1.0 W cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…PANoptosis serves as a critical protective mechanism for cells exposed to various stresses and injuries; thus, activation of PANoptosis may render cancer cells more susceptible to treatments and thereby improve therapeutic outcomes [ 109 ]. Currently, PANoptosis is widely acknowledged as an inflammatory form of PCD governed by the PANoptosome complex [ 15 ].…”
Section: Therapeutic Applications Of Panoptosis In Cancermentioning
confidence: 99%
“…Emerging research highlights PANoptosis as a signi cant aspect of cellular demise, integrating pyroptosis, apoptosis, and necroptosis (Shi et al, 2023; X. Sun et al, 2024). Regulated by a cascade of upstream receptors and molecular signals, PANoptosis operates through the PANoptosome complex, offering potential intervention targets for disease management (Sundaram et al, 2023; M. Zheng & Kanneganti, 2020).…”
Section: Introductionmentioning
confidence: 99%